Ways of energy saving during thermal and chemicalthermal treatment of steel due to acceleration of diffusion processes - V. M. Konstantinov; V. A. Kukareko (Литьë и металлургия)
Some technical and economically effective ways of energy saving in the processes of thermal and chemical‑thermal treatment of steels are analyzed. A classification of ways to save energy by activating structural‑phase transformations in steels is proposed. The results of work on accelerating diffusion processes in steels during thermal improvement, thermal cycling treatment, thermal diffusion galvanizing, nitriding and carburization are summarized. A high potential for energy saving and increased productivity by reducing the time of thermal and chemical‑thermal treatment was noted.